Utilization Of Petai Peel (Parkia Speciosa Hassk.) Extract In Spray Formulation As A Mosquito Repellent Against Aedes Aegypti - Linda Septiani; Selvi Marcellia; Muhammad Maulana; Reny Arienta Putri; Michelle Safna Andari; Terza Aflika Happy; Nurul Hidayati; Arif Setiawansyah; Endah Setyaningrum; Emantis Rosa (Politeknik Kesehatan Kemenkes Mamuju, 2026)
Mosquitoes act as vectors of disease in humans. One method to break the chain of transmission is to reduce contact between humans and mosquitoes by using repellents. Currently, several repellents on the market contain chemicals that are harmful to users and the environment. Some researchers have conducted studies as an alternative to replace the chemicals contained in repellents by utilising extracts from natural materials. One part of the plant that is thought to have potential as a repellent is petai peel waste (Parkia speciosa Hassk.), which contains several bioactive compounds. The purpose of this study was to determine the effectiveness of petai peel waste extract in spray formulation as a repellent for Aedes aegypti mosquitoes. Extraction was carried out using the Ultrasonic Assisted Extraction (UAE) method with 96% ethanol solvent. The 25% petai peel extract formulation showed the highest repellent activity, providing over 91% protection during the first and second hours, although its effectiveness gradually declined over time, resulting in an overall average protection of 87.94%. Based on these results, petai peel waste extract has the potential to be developed as an environmentally friendly natural repellent, while also adding value to waste utilization and supporting mosquito control programs.